Meta-Analysis of the QTLome of Fusarium Head Blight Resistance in Bread Wheat: Refining the Current Puzzle - Venske, Eduardo; dos Santos, Railson Schreinert; Farias, Daniel da Rosa; Rother, Vianei; da Maia, Luciano Carlos; Pegoraro, Camila; Costa de Oliveira, Antonio (Frontiers in Plant Science, 2019)
Background - Fusarium Head Blight (FHB) is a worldwide devastating disease of bread wheat (Triticum aestivum L.). Genetic resistance is the most effective way to control FHB and many QTLs related to this trait have been mapped on wheat genetic map. This information, however, must be refined in order to be more efficiently used in breeding programs and for the advance of the basic research. The objective of the present study was to in-depth analyze the QTLome of FHB resistance in bread wheat, further integrating genetic, genomic and transcriptomic data, aiming to find candidate genes. Methods - An exhaustive bibliographic review on 76 scientific papers was carried out collecting information about QTLs related to FHB resistance mapped on bread wheat. A dense genetic consensus map with 572,862 loci was generated for QTL projection. Meta-analysis could be performed on 323 QTL. Candidate gene mining was carried out within the most refined loci, being these genes cross-validated with publicly available transcriptional expression data of wheat under FHB infection. Most highlighted genes were investigated for protein evidence. Results - A total of 556 QTL were found in the literature, distributed on all sub-genomes and chromosomes of wheat. Meta-analysis generated 65 meta-QTL, which refinement allows one to find markers more tightly linked to these regions. Candidate gene mining within the most refined meta-QTL, meta-QTL 1 / chr. 3B, harvested 324 genes and transcriptional data cross-validated 10 of these genes, as responsive to FHB. One is of these genes is coding for a Glycosiltransferase and other to Cytochrome P450, which proteins have been already verified as responsible for FHB resistance, but the remaining eight genes have still to be further studied, as promising loci for breeding. Conclusions - The QTLome of FHB resistance in wheat was successfully assembled and a refinement in terms of number and length of loci was obtained. The integration of the QTLome with genomic and transcriptomic data has allowed for the discovery of promising candidate genes for use in breeding programs.